Implementation of Local Wisdom Values as a Managerial Approach in Strengthening Public Health Programs (Oshada, 2025)
Strengthening community health programs requires managerial approaches that are not only technically effective but also culturally and socially contextualized. This study aims to analyze the implementation of local wisdom values as a managerial approach in strengthening community health programs and its implications for health behavior, social participation, and program sustainability. The study employs a qualitative approach with a multiple case study design through in-depth interviews, participant observation, and document analysis involving health stakeholders and local communities. Data were analyzed using thematic analysis to identify patterns of implementation, challenges, and impacts of integrating local wisdom. The findings reveal that local wisdom enhances policy legitimacy, strengthens community trust, promotes sustainable healthy behaviors, and increases community participation and program sustainability. However, its implementation continues to face institutional constraints, limited managerial capacity, and policy misalignment. This study underscores that integrating local wisdom constitutes a strategic foundation for building adaptive, equitable, and sustainable community health systems.